(untitled) (TAMADDUN NURI JURNALI, 2025)
The article analyzes the importance of family stability and intergenerational continuity. The transmission of traditional values from generation to generation is considered a key factor in strengthening the institution of the family. The educational process, cultural heritage, and social norms are shaped through family continuity. Strong connections between generations also influence societal stability. The research results show that the preservation of family values contributes to social development.